Left Behind but Doing Good? Civic Engagement in Two Post-Socialist Countries - Milena Nikolova; Monica Roman; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2015)
The fall of socialism in Central and Eastern Europe restored ordinary citizens' rights and freedoms and ended their political and social isolation. While the freedom of movement was quickly embraced, civil society revival lagged due to the eroded civic norms, declining social capital, and worsening economic conditions. In this paper, we examine the link between the out-migration of relatives and friends and the pro-social behavior of the left behinds in two post-socialist countries – Bulgaria and Romania – the EU's poorest, unhappiest, and among the most corrupt members. We show that having close contacts abroad is consistently positively associated with civic engagement and that the cultural transmission of norms from abroad could be driving the results. Specifically, the strength of the civic engagement culture of the family or friend's destination matters for the pro-social behavior of respondents in the home countries. Our results imply that the emigration of family and friends may have positive but previously undocumented consequences for the individuals and communities left behind in Bulgaria and Romania. Given civil society's role for development in post-socialist Europe and the socio-economic and institutional challenges that Bulgaria and Romania face compared with the rest of the EU, understanding the channels fostering civil society and well-being are important for national and EU policymakers.
Keywords: I30; I31; F22; P30; Z10; 330; international migration; left behind; civic engagement; social remittances; post-socialism